Biocatalysts for biomass deconstruction from environmental genomics. (December 2015) - Armstrong, Zachary; Mewis, Keith; Strachan, Cameron; Hallam, Steven J
Highlights: This paper reviews extant functional metagenomic screens for biomass deconstructing enzymes. Bioinformatic and screening methods are described in relation to gene discovery and strain engineering. The recovery of biological devices is discussed in relation to modular biomass deconstruction processes. Constructing biomass deconstructing ecosystems based on ecological design principles is considered. Abstract : Plant biomass offers a sustainable alternative to the energy and materials produced from fossil fuels. The industrial scale production or biorefining of fermentable sugars and aromatics from plant biomass is currently limited by the lack of cost effective and efficient biocatalysts. One potential solution to this problem is the discovery of biomass deconstructing biocatalysts from uncultivated microbial communities. Here we review recent progress in recovering such biological devices from environmental genomes and consider how this information can be used to build better biorefining ecosystems.